2008
DOI: 10.1021/ie071161f
|View full text |Cite
|
Sign up to set email alerts
|

Separation Performance of Nanoporous Carbon Membranes Fabricated by Catalytic Decomposition of CH4 Using Ni/Polyamideimide Templates

Abstract: Using a Ni/polyamideimide sol as a template, a nanoporous carbon membrane was prepared in a single coating by means of a novel technique:  the carbonization of a nickel-containing polyamideimide precursor combined with the catalytic decomposition of methane in a nitrogen atmosphere. The separation performance of the membrane was significantly better than that fabricated by a single coating and conventional pyrolysis, even as good as or better than those for three-coating carbon membranes. This procedure signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 46 publications
(72 reference statements)
1
3
0
Order By: Relevance
“…We also observed H 2 adsorption in the molecular or atomic state on NPCMs in H 2 TPD studies. 40 The permeations of gases through M 3 increased gradually with increasing temperature, in accordance with the activated diffusion mechanism, indicating that the diffusion of gases through M 3 exceeded the range of Knudsen diffusion. According to the surface diffusion or molecular sieving mechanism, the permeation of gases through membranes depends strongly on the apparent activation energy or the kinetic diameter of the gas.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…We also observed H 2 adsorption in the molecular or atomic state on NPCMs in H 2 TPD studies. 40 The permeations of gases through M 3 increased gradually with increasing temperature, in accordance with the activated diffusion mechanism, indicating that the diffusion of gases through M 3 exceeded the range of Knudsen diffusion. According to the surface diffusion or molecular sieving mechanism, the permeation of gases through membranes depends strongly on the apparent activation energy or the kinetic diameter of the gas.…”
Section: Resultssupporting
confidence: 53%
“…However, the permeation of H 2 through M 2 increased slightly with increasing temperature because of the adsorption of H 2 on the NPCMs and the increasing tendency of H 2 to be adsorbed at higher temperatures. We also observed H 2 adsorption in the molecular or atomic state on NPCMs in H 2 TPD studies …”
Section: Resultsmentioning
confidence: 69%
“…In the present study, Fig. 4 shows a change of slope at T À1/2 ¼ 0.054 K À1/2 which corresponds to 60 C. Liu et al [35] reported 50 C as a limiting temperature where both gas adsorption and diffusion coexist, with adsorption being predominant at the lowest temperature.…”
mentioning
confidence: 76%
“…Recently, the surface modification of the conventional substrates has become more popular, for example, to coat a fine-porous ceramic surface layer on the substrate, which aims at reducing surface pore-size, repairing surface defects and decreasing surface roughness [10,27,28]. So far, many approaches have been developed to coat a fine-porous ceramic surface layer, including solgel [14][15][16][17], chemical vapour deposition [18], wet powder spray [19], thermal spray [20,21], and magnetron sputtering [22]. Unfortunately, the high cost of these processes often offsets or even exceeds the cost that is saved through the application of less expensive substrate materials.…”
Section: Introductionmentioning
confidence: 99%